A Membrane‐Targeting Photosensitizer with Aggregation‐Induced Emission Characteristics for Highly Efficient Photodynamic Combat of Human Coronaviruses. Issue 30 (30th June 2021) - Wu, Ming‐Yu; Gu, Meijia; Leung, Jong‐Kai; Li, Xinmei; Yuan, Yuncong; Shen, Chao; Wang, Lianrong; Zhao, Engui; Chen, Sijie
Abstract: COVID‐19 pandemic, caused by severe acute respiratory syndrome coronavirus 2, has resulted in global social and economic disruption, putting the world economy to the largest global recession since the Great Depression. To control the spread of COVID‐19, cutting off the transmission route is a critical step. In this work, the efficient inactivation of human coronavirus with photodynamic therapy (PDT) by employing photosensitizers with aggregation‐induced emission characteristics (DTTPB) is reported. DTTPB is designed to bear a hydrophilic head and two hydrophobic tails, mimicking the structure of phospholipids on biological membranes. DTTPB demonstrates a broad absorption band covering the whole visible light range and high molar absorptivity, as well as excellent reactive oxygen species sensitizing ability, making it an excellent candidate for PDT. Besides, DTTPB can target membrane structure, and bind to the envelope of human coronaviruses. Upon light irradiation, DTTPB demonstrates highly effective antiviral behavior: human coronavirus treated with DTTPB and white‐light irradiation can be efficiently inactivated with complete loss of infectivity, as revealed by the significant decrease of virus RNA and proteins in host cells. Thus, DTTPB sensitized PDT can efficiently prevent the infection and the spread of human coronavirus, which provides a new avenue for photodynamic combating of COVID‐19. Abstract : In this work, we report the application of a novel photosensitizer, DTTPB, with aggregation‐induced emission characteristics for photodynamic inactivation of human coronaviruses. With high molar absorbance coefficient, broad absorption band covering the whole white light region, and high membrane targeting and ROS sensitizing efficiency, DTTPB could effectively inactivate human coronaviruses and may contribute to preventing the spread of COVID‐19 pandemic.